Using African Ubuntu theory in social work with children in Zimbabwe - Mugumbate, Jacob; Chereni, Admire (National Association of Social Workers, 2021)
Using indigenous knowledge systems such as Ubuntu in social work with children empowers them, their families, communities and workers. Yet, the potential of using frames that draw on indigenous ways of knowing, in children’s work, remain unrealised since social workers prefer Western models and theories. Ubuntu inspired models of social work view children from family, community, environmental and spiritual perspectives. In contrast, Western models are inspired by individualitic values, governmental policies and professional viewpoints. However, as will be shown in this article, foreign models have failed to live up to expectations because they tend to disempower and diminish the strengths of everyone involved in case situations. For example, the social worker has to administer a model that they are not fully familiar with or which contradicts their own values. The family is forced to adopt values that they do not know let alone believe in. The community becomes powerless in the process. This article discusses the use of Ubuntu theory in social work with children in Africa. The discussion includes five frameworks of Ubuntu: the orature, scholarly, liberation, practice and integrated. The Ubuntu inspired Zera model of child growth and development was used to aid the discussion. We conclude that, given social work’s emphasis on using strengths perspectives, i.e., those broader frames that deliberately look for and build on the strengths of clients and client systems, social work practice with children in Africa should engage with Ubuntu, as a matter of principle..